P25 A new England-wide survey on quality of life after cancer. (26th August 2022) - Frobisher, Clare; Judge, Charlotte; Gildea, Carolynn; Phillips, Lucinda; Ratchford, Daniel; Raphael, Hannah; Shilling, Val; Smout, Fadzai; Rosenberg, Gillian; Rogers, Simon
Abstract : Background: There is a growing appreciation of the importance of quality of life (QoL) alongside survival of cancer. The 2019 NHS Long Term Plan highlights the need to: 'Introduce an innovative QoL metric to track and respond to the long-term impact of cancer'. A cancer QoL Survey has been jointly initiated by NHS England and NHS Improvement, and NDRS at NHS Digital, with Quality Health managing invites and responses (http://www.cancerqol.england.nhs.uk/index.html). Methods: Patients (≥16 years old) are identified 18 months post-diagnosis from the National Cancer Registration Dataset in England. Each month, newly eligible patients are invited to complete the survey online, with a reminder and paper copy sent 3 weeks later. The survey uses the validated EQ-5D-5L and EORTC QLQ-C30 QoL instruments. From September 2020, the QoL survey was piloted for 10% of breast, colorectal and prostate cancer cases, with expansion to all cases for these cancers from December 2020. From July 2021, a pilot of 10% of all other cancer cases was included, before expansion to all cancer cases (ICD-10 C00-C97 excluding C44) from October 2021. Results: 108, 416 questionnaire invites, up to December 2021, have been sent and 53, 960 responses received by 15/02/2021 (response rate 50%). By cancer site, the response rates (number of responses/invites) are: breast 48% (18, 202/37, 718); colorectal 51% (10, 288/20, 195); prostate 54% (19, 260/35, 371); and all other cancer sites 41% (6, 210/15, 132). Results from the QoL are presented in a public-facing dashboard (https://www.cancerdata.nhs.uk/cancerqol), which allows comparisons of survey responses to general population data and filtering by cancer site and geography. QoL comparisons by patient factors are also possible e.g. age and sex. For invites September 2020-July 2021 (responses received by 12/09/2021), breast, colorectal and prostate cancer respondents rate their overall health (EQ-5D-5L Index) highly (mean (95% CI): 75.2 (75.0–75.5)), but lower than the general population (81.8 (81.3–82.3), p<0.001). They are significantly more likely to report a problem across all five aspects of health than the general population: mobility 40.2% (95% CI: 39.7–40.8%) vs 24.0% (23.0–25.0%); self-care 16.6% (16.2–17.0%) vs 8.5% (7.9–9.2%); usual activities 47.6% (47.1–48.2%) vs 21.8% (20.8–22.7%); pain and discomfort 60.9% (60.4–61.5%) vs 48.6% (47.4–49.7%); and anxiety and depression 47.9% (47.3–48.4%) vs 33.1% (32.0–34.2%). These differences are particularly marked for usual activities. Conclusion: This survey is the first to give detailed, continuous data on the impact of cancer on QoL and will help to empower patients, and to inform research and the improvement of cancer services.